Evaluating the experiences and support needs of people living with chronic cancer: development and initial validation of the Chronic Cancer Experiences Questionnaire (CCEQ). Issue 1 (10th August 2016) - Harley, Clare; Pini, Simon; Kenyon, Lucille; Daffu-O'Reilly, Amrit; Velikova, Galina
Abstract : Background: Many advanced cancers are managed as chronic diseases, yet there are currently no international guidelines for the support of patients living with chronic cancer. It is important to understand whether care and service arrangements meet the needs of this rapidly growing patient group. This study aimed to develop and validate a questionnaire to capture patients' experiences of living with chronic cancer and their views of clinical and support services. Methods: The research was carried out between 1 July 2010 and 21 February 2013. A conceptual framework and initial item bank were derived from prior interviews with 56 patients with chronic cancer. Items were reviewed by 4 oncologists and 1 clinical nurse specialist and during 2 focus groups with 9 patients. Pilot questionnaires were completed by 416 patients across 5 cancer units. Item selection and scale reliability was explored using descriptive data, exploratory factor analysis, internal consistency analyses, multitrait scaling analyses and known-groups comparisons. Results: The final Chronic Cancer Experiences Questionnaire (CCEQ) includes 75 items. 62 items contribute to 14 subscales with internal consistency between α 0·68–0·88 and minimal scaling errors. Known-groups comparisons confirmed subscale utility in distinguishing between patient groups. Subscales were labelled: managing appointments, coordination of care, general practitioner involvement, clinical trials, information and questions, making treatment decisions, symptom non-reporting, key worker, limitations, sustaining normality, financial advice, worries and anxieties, sharing feelings with others, and accessing support. 13 items assessing symptom experiences were retained as single items. Conclusions: The CCEQ has the potential to be used as a clinical instrument to assess patient experiences of chronic cancer or to screen for patient needs. It may also be used as an outcome measure for evaluating programmes and models of care and may identify areas for service development that could ultimately improve the care and support received by patients with chronic cancer.